Udział polskich ziemian z Mińszczyzny w pracach rady nadzwyczajnej do spraw związanych z potrzebami gospodarki rolnej w Rosji w latach 1902-1903: Participation of Polish landowners from Minsk guberniya in the work of the Extraordi-nary Council for matters connected with the needs of agriculture in Russia, in 1902-1903 - Jurkowski, Roman (Przegląd Wschodnioeuropejski, 2021)
The article presents an unknown period from the history of the Polish gentry from the Taken Lands at the beginning of the 20th century. It shows the participation of Polish landowners in the work of the Extraordinary Council for matters connected with the needs of agriculture in the Minsk guberniya in 1902-1903, the purpose of which was to describe the state of agriculture in Russia and to indicate ways of its modernization. The Polish landowners, gathered in the Minsk Agricultural Society, were the most active element among all members of the 9 discrits committees in the Minsk guberniya. For the first time since the fall of the January Uprising, they had the opportunity to show their organizational skills and substantive preparation for the discussion on the situation of agriculture in the Minsk guberniya.